Oropharyngeal Dysphagia Patient Profile Based on Flexible Endoscopic Evaluation of Swallowing - Chairul Anhar; Rizka Fathoni Perdana; Mohd Razif Mohamad Yunus (Biomolecular and Health Science Journal)
Introduction: Oropharyngeal dysphagia is a swallowing disorder in the oral and/or pharyngeal phase. The prevalence of oropharyngeal dysphagia is higher when there is the presence of comorbid conditions such as head-and-neck cancer (19%–81%) and neurological diseases (Parkinson’s [80%–100%] and stroke [19%–81%]). Methods: This retrospective descriptive study used medical record data from the outpatient clinic of the Otorhinolaryngology-Head and Neck Surgery Unit in the Broncho Esophagology Division of Dr. Soetomo General Academic Hospital from January 2018 to December 2019. Results: In total, 112 patients met the inclusion and exclusion criteria. There were more male (61.60%) than female (38.4%) patients, at a ratio of 1.6:1. The most common age group was 50–90 years old (66.0%). The most common chief complaint was choking (37.5%). The highest risk factor was stroke (25.9%). Preswallowing: velopharyngeal movement (14.4%), vocal cord movement disorders (28.6%), standing secretion (83.9%), penetration (38.4%), aspiration (24.1%), silent aspiration (15.2%), and impaired hypopharyngeal sensitivity (33%). Swallowing solid bolus test: residual (78.9%), penetration (23.2%), aspiration (18.9%), and impaired cough reflex (82.1%). Swallowing liquid bolus test: residual (76%), penetration (24%), aspiration (12.7%), and impaired cough reflex (91.1%). Conclusion: Men more than women are affected by this disease. The most common age group was >50 years. The most common complaint is choking. Stroke is the most common etiology. Impaired vocal cord movement, standing secretion, penetration, and silent aspiration were found on the preswallowing test. Residues are more common in solid boluses than liquid. Liquid bolus penetration is more common than solid. The aspiration of solid boluses is more common than that of liquid.